Information Technology Audit in Georgia - Beridze, Tamta (European Scientific Journal, ESJ, 2017)
With the development of information technology to carry out effectively their missions the largest part of a variety of organizations, government agencies and services have become dependent on computer systems. For each of the organization’s activities the IT environment must be properly studied and evaluated in which they perform the basic activities. Therefore, in such environment it is necessary to make the information technology audit of IT systems operating reliability and functionality in order to obtain reasonable assurance. IT governance and information systems audit is imperative for successful governance. This paper with a comprehensive literature review defines information technology audit, investigates how IT audit performs in the public sector of Georgia. Also it provides the thorough explanation of the experiences of the Georgian State Audit Office. The study analyses the challenges of the IT audit and point to future development directions of IT audit in the public sector. Although considerable research exists on IT control and on internal auditing, there is limited study that refers to IT evaluation control activities in the public sector auditing. As such, the findings from this research would generate new conclusion to enrich the existing literature on IT related auditing. The findings also may improve the IT evaluation activities in the Georgian public sector.